The community economics shaping alternative spaces of Islamic futurity in Singapore - WOODS, Orlando (Institutional Knowledge at Singapore Management University, 2024)
This chapter explores the importance of community formation and cohesion as a barometer for the economic viability of religious groups. The idea of “community economics” encapsulates this viability and encompasses both its material and ideological dimensions. I illustrate the trade-offs and negotiations that emerge when state-defined visions of religious community differ from citizen-defined visions. The interplay between state and society reveals new visions of religious futurity that are forged through the interstices of regulation and praxis. I illustrate these ideas through an empirical exploration of Islamic community-building in Singapore. In Singapore, the state plays an outsized role in the regulation of religious—particularly Muslim—community, the aim being to forge a cosmopolitan national identity and maintain a sense of religious harmony. Accordingly, efforts are made to standardize sermons, circulate imams, and create a culture in which mosque attendance is imbued with functionalist meaning. These ideological impulses render many mosques economically unviable. In response, mosques rely on the volunteer labor of Bangladeshi migrant workers to maintain their liveliness, operation, and upkeep. This reliance offers alternative visions of Islamic futurity in Singapore that go beyond state-centricity.